Psychological Attitudes towards Electronic learning in Female and male Students of Physical Education and Sport Sciences / University of Baghdad - Muhameed Qasim; Tamadur Abdulazeen (College of Physical Education and Sport Sciences, 2021)
The research aimed at identifying the psychological attitudes of students in the college of physical education and sport sciences'/ university of Baghdad. The researchers used a psychological attitude towards electronic learning constructed by Mohammed Qasem to identify the marks that the students get. The subjects were (259) female and male students and the scale was applied to them to conclude that the grades of psychological attitudes towards electronic learning are very low in second, third, fourth-year students while in first-year students the grades were high. Finally, the researchers recommended the necessity of changing programs and styles that teachers use as well as holding training courses to uplift their level of learning.